Impact of Korean Brand Ambassadors on Purchase Decisions at Tokopedia - Safitri, Zidan Egi; Santoso, Muhammad Ragil; Rofilla, Asfa (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2024)
This research examines the impact of Korean brand ambassadors on consumer purchasing decisions on Tokopedia using the Systematic Literature Review (SLR) method following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Literature analysis from 2019 to 2024 shows that Korean brand ambassadors have a significant influence on consumer purchasing decisions, especially among the younger generation. Brand ambassadors not only increase purchasing interest, but also strengthen brand image, which ultimately increases consumer loyalty. This study also found that the effectiveness of brand ambassadors is influenced by other factors such as marketing strategies on social media, competitive product prices, and positive reviews from consumers. In addition, the integration of brand ambassadors with other marketing elements such as creative and relevant advertising content strengthens the emotional connection between consumers and brands. The results of this research emphasize the importance of synergy between the use of brand ambassadors and other marketing strategies in driving purchasing decisions on e-commerce platforms such as Tokopedia.